Modeling the Timing of Antilatency Drug Administration during HIV Treatment - Petravic, Janka (J Virol, 2014)
Latently infected cells are considered a major barrier to the cure of HIV infection, since they are long-lived under antiretroviral therapy (ART) and cause viral replication to restart soon after stopping ART. In the last decade, different types of antilatency drugs have been explored with the aim of reactivating and purging this latent reservoir and the hope of achieving a cure. Because of toxicity and safety considerations, antilatency drugs can only be given for a short time to patients on long-term ART, with little effect. We recently investigated the turnover of latently infected cells during active infection and have found that it was strongly correlated with viral load. This implies that although latently infected cells had long life spans in a setting of a low viral load (such as during ART), they turned over quickly under a high viral load. Possible reasons for this could be that an increased viral load causes increased activation or death of CD4(+) T cells, including those that are latently infected. Taking these results into account, we developed a mathematical model to study the most appropriate timing of antilatency drugs in relationship to the initiation of ART. We found that the best timing of a short-term antilatency drug would be the start of ART, when viral load, CD4(+) T cell activation, and latent cell turnover are all high. These results have important implications for the design of HIV cure-related clinical trials. IMPORTANCE The antiretroviral therapy (ART) of HIV-infected patients currently needs to be lifelong, because the cells latently infected with HIV start new rounds of infection as soon as the treatment is stopped. In the last decade, a number of different types of antilatency drugs have been explored with the aim of “reactivating” and “purging” this latent reservoir and thus achieving a cure. These drugs have thus far been tested on patients only after long-term ART and have demonstrated little or no effect. We use mathematical modeling to show that the most efficacious timing of a short-term antilatency treatment may be the start of ART because of possible interactions of antilatency drugs with natural activation pathways.